THE RELATIONSHIP BETWEEN THE HEALTH BELIEF MODEL AND HYPERTENSION MEDICATION ADHERENCE: A SYSTEMATIC LITERATURE REVIEW - Nuzulul Nindya Kirana; Eko Winarti (Suluh Adiluhung Publisher (SAPub), 2026)
Hypertension control depends heavily on sustained medication adherence and self management, and poor adherence remains a major barrier to reducing cardiovascular morbidity and mortality. The HBM has been widely used to explain why patients engage in or avoid anti hypertensive treatment by focusing on perceived susceptibility, severity, benefits, barriers, self efficacy, and cues to action. The method used a library research method by critically reviewing academic oriented literature. There were 10 research journals adjusted to the literature review problem. The results show that the Health Belief Model is associated with hypertension treatment compliance, with the strongest support for improved short term adherence and blood pressure control in intervention studies, while observational studies show that the most predictive construct varies by population. Overall, the literature supports a positive but context-dependent relationship between the Health Belief Model and hypertension treatment compliance.